2014
DOI: 10.1177/0734242x14539789
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of biogas produced by anaerobic digestion of agro-industrial waste: Energy, economic and environmental effects

Abstract: Anaerobic digestion of agro-industrial waste is of significant interest in order to facilitate a sustainable development of energy supply. Using of material and energy potentials of agro-industrial waste, in the framework of technical, economic, and ecological possibilities, contributes in increasing the share of energy generated from renewable energy sources. The paper deals with the benefits arising from the utilization of biogas produced by co-digestion of whey and cow manure. The advantages of this process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 38 publications
0
15
1
2
Order By: Relevance
“…Anaerobic co-digestion of sewage sludge with other waste streams is an environmentally friendly and economically attractive method to overcome low biochemical methane potential of sewage sludge [13, 2128]. Hublin et al [21] revealed that anaerobic co-digestion of cheese whey and cow manure reduces CO 2 and CH 4 emissions by 3.5 ktonnes CO 2 /year and 5.7 ktonnes CO 2 -eq/year respectively. They, also, indicated that a medium-scale biogas plant is profitable for 12 and 15 year effectuation periods.…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobic co-digestion of sewage sludge with other waste streams is an environmentally friendly and economically attractive method to overcome low biochemical methane potential of sewage sludge [13, 2128]. Hublin et al [21] revealed that anaerobic co-digestion of cheese whey and cow manure reduces CO 2 and CH 4 emissions by 3.5 ktonnes CO 2 /year and 5.7 ktonnes CO 2 -eq/year respectively. They, also, indicated that a medium-scale biogas plant is profitable for 12 and 15 year effectuation periods.…”
Section: Introductionmentioning
confidence: 99%
“…Finalmente, en el proceso de residuos son principalmente estiércol (Mejías-Brizuela et al, 2016) utilizado para abonos orgánicos, mediante mezclas de cachaza y bagazo de caña de azúcar con diferentes fuentes de estiércol (Palma-López, Zavala-Cruz, Cámara-Reyna, Ruiz-Maldonado & Salgado-García, 2016); también en la producción de nano-celulosa a partir de la cáscara y pulpa de residuos cítricos (Naz et al, 2016); extracción de compuestos bioactivos de la cáscara de los cítricos como la lima (Padilla de la Rosa et al, 2018), pectina a partir del bagazo de lima (Sanchez-Aldana, Aguilar, Nevarez-Moorillon & Esquivel-Contreras, 2013) y los polifenoles obtenidos de las cáscaras de mandarina (Safdar et al, 2017). Sin embargo, la tendencia actual se inclina por la producción de bioenergía y biocombustibles, por ejemplo la obtención del biogás a partir de lacto-suero y estiércol de vaca, entre otros (Hublin, Schneider & Dzodan, 2014).…”
Section: Producción De Biogásunclassified
“…Elaiyaraju & Partha (2016) A partir del biogás purificado se puede generar electricidad, calor y combustible con fines de transportación (Elaiyaraju & Partha, 2016). Se estima que a partir de 1m 3 del mismo se puede producir 1.9 kW*h de energía en forma de electricidad, así como 3.8 kW*h de calor (Hublin et al, 2014). En términos comparativos, 1 m 3 de biogás al 60% de CH 4 equivaldría a 0.7 L de gasolina, 2.4 kW*h de electricidad, 0.6 m 3 de gas natural y 1.3 Kg de madera utilizada para producirlo (Ponce, 2016).…”
Section: Bioenergía Y Biocombustiblesunclassified
“…This is clearly reflected by a literature review of the previous SDEWES special issues which include a large number of papers investigating this topic, summarized in the following Table 4. In this field, biogas and gasified biomass are probably the most promising bio-fuels for their potential to decarbonize energy systems [116][117][118][119]. Gaida et al [105] presented a detailed review of different strategies to control substrate feed in anaerobic digesters.…”
Section: Biomassmentioning
confidence: 99%